Evaluating a framework for making outsourcing decisions in pharmaceutical clinical trial operations - Granger, Monique (2021)
This research aims to evaluate a framework to support outsourcing decisions within the pharmaceutical clinical development industry. Outsourcing is the movement of an “inhouse process to an external vendor” (Click & Duening, 2005). As evidenced by the literature review in sections 2.1, 2.5 and 2.7, much of the prior outsourcing decision-making research has been performed in the manufacturing industry settings, with limited research done in the pharmaceutical R&D service delivery sector. Efficiency in supplier selection and risk mitigation contribute to outsourcing success and meeting business objectives (Lee, 2020). The pharmaceutical clinical development industry is increasingly reliant on different outsourcing models (section 2.9) to support its operations, cost reduction strategies and speed of development (Bouch, 2020). Failure to manage the outsourcing partnership, can lead to outsourcing failure rates of up to 70% (Zineldin & Bredenlow, 2003). The type of outsourcing relationship (section 2.3) will be determined by the type and scope of the outsourced processes (Obwegeser, et al., 2020). The ability to supply managers with a holistic framework to support making outsourcing decisions, may result in reduced time and increased outsourcing success and address a need identified within the pharmaceutical research industry. This research will include a literature review on outsourcing, pharmaceutical drug development and outsourcing frameworks in chapter 2. In chapter 3, the methodology will be explained, and the case study reviewed against the selected framework. In chapter 4 the findings and recommendations from this research will be discussed, which will be followed by the conclusion in chapter 5.